Imitation Artist : Gertrude Hoffmann's Life in Vaudeville and Dance - Stalter-Pace, Sunny, 1977- (Book collections on Project MUSE., 2020)
"Imitation Artist: Gertrude Hoffmann's Life in Vaudeville and Dance is the first book-length study of Gertrude Hoffmann's long and influential career as a performer and producer. Hoffmann made her name in the early twentieth century as an imitator, copying highbrow performances from Europe and popularizing them for a broader American audience. Born in San Francisco, Hoffmann started working as a ballet girl in pantomime spectacles during the Gay Nineties. She performed through the heyday of vaudeville, then taught dancers and choreographed for nightclub revues. After her career ended, she reflected on how vaudeville's history was represented in film and television. Drawn from extensive archival research, Imitation Artist shows how Hoffmann's life intersected with that of central figures in twentieth-century popular culture and dance including Florenz Ziegfeld, George M. Cohan, Isadora Duncan, and Ruth St. Denis. Hoffmann navigated the complexities of performing gender, race, and national identity at the dawn of contemporary celebrity culture. Imitation Artist is essential reading for those interested in the history of theater and dance, modernism, women's history, and copyright"--